Impact of entamopathogenic fungal infection on the detoxifying enzyme in cotton leaf worm, Spodopteralitura(fabricius) - VIDHYA, D; P. RAJIV; NALINI PADMANABHAN (International Journal of Pharma and Bio Sciences, 2016)
The army worm Spodoptera litura (Fabricius) is one of the most destructive polyphytophagus crop pests in Indian sub-continent. The present study aims to investigate the effect of three fungal pathogens Beauveria bassiana, Metarhizium anisopliae and Verticillum lecanii on the total protein content and also on detoxifying enzymes like Glutamic Pyruvic Transaminase (GPT), Glutamic Oxaloacetate Transaminase (GOT), Alkaline Phosphatase (ALP) and Acid Phosphatase (ACP) and Acetylcholine esterase (AChE). The 48 and 96 hrs post infected larvae were used for evaluation. Throughout the study there was significant changes in the level of protein, GPT, GOT, ALP, ACP and AchE indicate very high elevations in both Beauveria bassiana and Metarhizium anisopliae treated larvae. Hence there is no significant elevation in Verticillum lecani treated larvae. It is proved by the results that these fungal pathogens cause significant inhibition of metabolic enzymes.